Design of Malaysian fishing vessel for minimum resistance - Yaakob, Omar; Teoh, Eng Lee; Liew, Yek Wai; Koh, Kho King (Penerbit UTM Press, 2005)
Due to the economic and operational reasons, there is a need to reduce resistance of fishing boats. One of the ways to reduce resistance is to modify the boat hull form to reduce its drag in water. However, designers normally have problems in choosing which hull form parameter to change, in which direction, and the degree of changes required. This paper describes a methodology of incorporating resistance optimization in the design of fishing boats. By producing easily understood design charts, the designer is guided in making his choice. An example of application of this method on the design of a Malaysian fishing boat is given. It is shown that by using this method, the hull can be modified without changing the principal dimensions and displacement and this slight modification of the hull form can produce up to 12% saving in fuel consumption.